Expanding genotype/phenotype of neuromuscular diseases by comprehensive target capture/NGS. (August 2015) - Tian, Xia; Liang, Wen-Chen; Feng, Yanming; Wang, Jing; Zhang, Victor Wei; Chou, Chih-Hung; Huang, Hsien-Da; Lam, Ching Wan; Hsu, Ya-Yun; Lin, Thy-Sheng; Chen, Wan-Tzu; Wong, Lee-Jun; et al.
Abstract : Objective: To establish and evaluate the effectiveness of a comprehensive next-generation sequencing (NGS) approach to simultaneously analyze all genes known to be responsible for the most clinically and genetically heterogeneous neuromuscular diseases (NMDs) involving spinal motoneurons, neuromuscular junctions, nerves, and muscles. Methods: All coding exons and at least 20 bp of flanking intronic sequences of 236 genes causing NMDs were enriched by using SeqCap EZ solution-based capture and enrichment method followed by massively parallel sequencing on Illumina HiSeq2000. Results: The target gene capture/deep sequencing provides an average coverage of ∼1, 000× per nucleotide. Thirty-five unrelated NMD families (38 patients) with clinical and/or muscle pathologic diagnoses but without identified causative genetic defects were analyzed. Deleterious mutations were found in 29 families (83%). Definitive causative mutations were identified in 21 families (60%) and likely diagnoses were established in 8 families (23%). Six families were left without diagnosis due to uncertainty in phenotype/genotype correlation and/or unidentified causative genes. Using this comprehensive panel, we not only identified mutations in expected genes but also expanded phenotype/genotype among different subcategories of NMDs. Conclusions: Target gene capture/deep sequencing approach can greatly improve the genetic diagnosis of NMDs. This study demonstrated the power of NGS in confirming and expanding clinical phenotypes/genotypes of the extremely heterogeneous NMDs. Confirmed molecular diagnoses of NMDs can assist in genetic counseling and carrier detection as well as guide therapeutic options for treatable disorders.